DAMPAK DAN PENGARUH MEDIA KOMUNIKASI SOSIAL SERTA TEKNOLOGI INFORMASI TERHADAP PERKEMBANGAN ANAK - Dominikus I Gusti Bagus Kusumawanta (Bahasa Indonesia, 2018)
Today, the presence of Information and Communication Technology has changed the pattern of social and interpersonal communication excites the faithful. At the same time, social communication technology has been used to move the joints of life, as well as a variety of works and other businesses. At present, the Church is undergoing various benefits of the Information Technology and Social Communication, among others: Proclaiming the Gospel is increasingly widespread, more intensive communication despite people separated by distance and the solidarity movement is increasingly assuming a place in the hearts of the people. Social Information and Communication Technology has brought the Church through the media, both print media, such as newspapers, magazines and tabloids, as well as electronic media such as radio, TV, Smartphone, Computer, Internet with a variety of its application. Thus, the Church can be known and heard by the public voice. Communication whatsoever and howsoever various forms has opened a wider horizon for many people. Communication is a gift from God that must be accountable to God and others. Man with the Media of Social Communications can glorify God and uphold human dignity, but it also can be distanced from God and injure human dignity. Like a double-edged knife with positive and negative impacts as well. Media Communication with rapid information technology should be utilized as an opportunity and not a threat to the progress of the Church and society. Media communication should bring closeness and human encounters that resulted in the betterment of life and human well-being